Participation of religious women in the creation of the nursing service in a university hospital (1909-2005) - Djailson José Delgado Carlos; Raimunda Medeiros Germano; Maria Itayra Padilha (Universidade Federal do Ceará, 2014)
This study aimed to analyze the participation of religious women in the creation of the Nursing service in a university hospital in Rio Grande do Norte, Brazil. This is a qualitative social-historical study, which considered as the period of study the years from 1909 to 2005, representing the beginning and the end of the presence of the sisters daughters of St. Anne in the institution. The research was based on survey in documents, reports, minutes, laws and decrees, ordinances, supplemented by interviews with ten professionals and religious women, who worked at the hospital from the 1950s on. It was concluded that the investigated reality coincides with the Brazilian context in terms of lack of preparation from those who act in Nursing; performance of religious women in the hospital and healthcare duties. The nuns daughters of St. Anne were the pioneers and responsible during decades for the internal administration of the hospital and patients' care.